A System for Developing The Skills of A Future Primary School Teacher in the Use Of Digital Educational Resources (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article tells about the formation of the readiness of the future primary school teacher to use digital educational resources and tells in detail how to solve this urgent pedagogical problem. In today's digital age, these ideas are becoming more and more important in the education system.